Penerapan Aplikasi Sistem Keuangan Desa (Siskeudes) Dalam Mencegah Terjadinya Tindak Pidana Korupsi Di Desa Karang Sentosa - Rahmi, korin; Azijah, Dewi Noor; Purnamasari, Hanny (Jurnal Administrasi dan Kebijakan Publik, 2022)
This study aims to analyze the application of the Village Financial System Application (SISKEUDES) in preventing the occurrence of criminal acts of corruption in Karang Sentosa Village, Karang Bahagia District, Bekasi Regency, West Java Province. This study uses a descriptive qualitative approach by collecting data using interviews and observations. The results showed that the implementation of the Village Financial System Application (SISKEUDES) brought quite good changes to the Karang Sentosa Village government by facilitating accurate accountability reporting by producing transparent and accountable financial reports, so as to prevent corruption by the Village Head. and other village officials.